Compreensão docente quanto as fases da psicossexualidade infantil - OLIVEIRA, Vanessa do Nascimento (2022)
This Course Conclusion Work aimed to describe, analyze and understand the teacher's view regarding the development of child sexuality according to Freud's Theory. A mixed methodology was used, being a Systematic Review and an empirical research. The corpus is composed of scientific articles identified in the Capes Database, using two descriptors: child sexuality AND teaching work; child sexuality AND school environment. The empirical research was carried out with three teachers of early childhood education in the city of Altamira-PA. The results showed that there is a lack of research published in Portuguese on the theme of child sexuality and teaching. Empirical data showed that there is a need for continuing education focused on themes found within the psychology of education that deepen knowledge about child psychosexuality, in order to have a better approach and management when necessary.